TRADISI LITERASI ISLAM DAN BUDAYA BACA MASYARAKAT ACEH - Imran Muhammad (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
Aceh is one area that implements Islamic law which is built on a strong foundation of literacy both memorized and written. Literacy is the capital of faith, a person can live well and truly supported by good and true literacy as well. Building a culture of literacy requires individual self-awareness, such as getting used to reading books, magazines, newspapers or other sources of information which are rare items in this technological era. The discussion about Islam as a representation of the literacy culture movement is that Islam has provided the initial foundation in the development of literacy culture, "Iqra 'which means to read!". As a representation, the caliphs Harun Al-Rasyid and Sultan Iskandar Muda have shown Aceh's progress in the field of literacy. The discussion about Islamic law and the reading culture of the Acehnese people was discussed through the implementation of Islamic law through educational institutions, the senior culture and the reading culture of the Acehnese people.